The Effectiveness of SISKOHAT in Organizing Hajj at the Ministry of Religious Affairs Office of Lima Puluh Kota Regency - Qolbi, Lora; Rahman, Ali (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Walisongo Semarang, 2023)
The Ministry of Religious Affairs Office of Lima Puluh Kota showed that the number of employees who could use SISKOHAT was only three people; hence, if many pilgrims registered on the same day, the employees at the Ministry of Religious Affairs Office of Lima Puluh Kota would have difficulty serving the pilgrims. The pilgrims would take a long time waiting in line. The research method used in this study was a qualitative descriptive approach. Data collection techniques were by observing, interviewing, and documentation. The participants in this study were employees of theMinistry of Religious Affairs Office of Lima Puluh Kota and one of the pilgrims who came to the Ministry of Religious Affairs Office of Lima Puluh Kota. The analytical method in this study started with data collection, data reduction, and drawing conclusions. The results of the study showed that SISKOHAT was running well, and system updates were being carried out in line with increasingly advanced technological developments in organizing the pilgrimage at the Directorate General of PHU at theMinistry of Religious Affairs Office of Lima Puluh Kota. The inhibiting factor of SISKOHAT that occurred at the Ministry of Religious Affairs Office of Lima Puluh Kota did not become a barrier for the staff of the Hajj and Umrah pilgrimage division. In addition, the government also anticipated so that it could prevent incidents that could hinder the effectiveness of information and computerized systems.